Black history collection - Robards, Lewis C.
Correspondence, speeches, writings, court records, legal documents, slave deeds, family papers, birth records, inventories, wills, military records, financial records, ship's papers, and marriage certificates pertaining to African Americans from the colonial period through the early twenty-first century. Topics include the slave trade, abolition, manumission, emancipation, medical care of slaves, civil rights, slaves, fugitive slaves, freedmen, free blacks, medical care of slaves, and African Americans serving in the Civil War and World War I.
Collection material in English, French, and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Includes a receipt book (1851 February 6-1853 May 23) of Lewis C. Robards that was formerly cataloged separately.
Keywords: Abolitionists; African Americans; Apprentices; Civil rights; Free blacks; Freedmen; Fugitive slaves; Registers of births, etc; Ship's papers; Slave records; Slave trade; Slavery; Slaves; Slaves -- Emancipation; Slaves -- Legal status, laws, etc; Slaves -- Medical care; Vital statistics; World War, 1914-1918 -- African Americans; United States -- History -- Civil War, 1861-1865 -- Participation, African American